Dr. Paula Audi — Deep Plane Facelift — Beirut - Audi, Paula (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Paula Audi, practicing in Beirut, Lebanon. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003076; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; lebanon; beirut